Aortic Isthmus Doppler For Fetal Assessment - Alev Esercan; Ruhat Karakuş; Ayşe Seval Özgü Erdinç (Medical Network, 2016)
Doppler assessment of fetal arteries provides information on regional blood flow and perfusion of individual organs, as well as giving insights into the fetal circulatory state in health and disease. Despite its important role in the fetal circulation, unlike ductus arteriosus; the aortic isthmus is not essential for intrauterine fetal survival. As gestation progresses, forward flow through the isthmus progressively decrease. Isthmic flow index (IFI), which reflects both the amount and direction of blood through this vascular segment, has 5 types. Positive and negative signs are assigned to antegrade and retrograde velocity values, respectively. Doppler flow recording in the aortic isthmus is a reliable indicator of fetal individual ventricular performance. In IUGR; an inverse association was found between IFI and postnatal neurodevelopmental outcome. Recent work on AoI Doppler and postnatal neurodevelopmental outcome indicates that predominant reversed diastolic blood flow. Further prospective studies correlating AoI indices and other arterial and venous Doppler indices with perinatal outcome are required prior to incorporating this index into clinical practice so as to avoid unnecessary preterm deliveries.